Assessment of Regulatory Requirements on Technological Changes: The Increasing Dominance of Downsized Turbo/Super-Charged Engines Over Naturally Aspirated Engines - Dong-Joon Lim; Dong-Hyuk Yang (IEEE Access, 2019)
Technological progress is often guided by new policies in an attempt to facilitate the desired future. The auto industry is no exception and is indeed continually advancing to meet increasingly stringent environmental standards that require a reduction in fuel consumption and greenhouse gas emissions. With the realization that the forced induction system is a viable solution that shows improved performance and complies with strict regulations, downsized turbo/super-charged (T/SC) engines have turned naturally aspirated (NA) engines into a niche technology. This paper employs a longitudinal efficiency analysis of internal combustion engines to assess the impact of regulations on technological changes in the 4-, 6-, and 8-cylinder segments over the past ten years. The results indicate that T/SC engines have further pushed their dominance in the technology frontier both in the compact segment and the luxury sports segment. If the current environmental and fuel economy regulations continue to become more stringent, a return to high-displacement unblown engines is unlikely to happen without a major breakthrough in NA technologies. We also show that the noticeable technological advancements have been made in 6-cylinder engines to fulfill the Euro 4 norm, while incremental progress has been made in the 4- and 8-cylinder engine segments.